THE CLASSROOM SOCIAL INTERACTION INFLUENCE ON THE NON-EFL STUDENTS IN ENGLISH SPEAKING CLASS - Destiani, Shendy; Indriani, Lilia; Kurniawan, Agung Budi (Universitas Islam Sumatera Utara (UISU), 2025)
Social interaction is one important factor that influences the process and resulting quality of non-EFL students in English-speaking classes. It could both support and decrease them. This study investigated the social interaction influences on the non-EFL college students’ English-speaking process and results. It aims to find out which social determinants cause students to engage communicatively in speaking tasks. The research was conducted by applying the qualitative descriptive design that involved observing classroom conduct, making field notes, and analyzing interactional processes to explore how students and lecturers built a social environment. The findings reveal four main data points that affected the quality of interaction, including the student noise and side-talk, non-routine greetings and leave-takings, mobile phone interference beyond control, and the lecturer’s management techniques in the classroom. The condition had an impact on the atmosphere of emotions through how students feel confident, focused, attentive, and motivated to talk. In general, the results emphasize the necessity of transparent social routines, behavioral guidance, and regulation in digital use to foster a good speaking environment in Indonesian higher institutions. It is suggested that mastering these non-pedagogical phenomena will be crucial for minimizing affective barriers and achieving speaking betterment, particularly in the case of developing communicative confidence among non-English majors.